desert plant ecology: desert plant ecology (jornal of the libyan geographical society, 2016)
There is considerable debate surrounding the laws of human behavior, largely due to the lack of clear experimental methods for understanding them. While animal and plant behavior can be studied both in nature and in the laboratory, and the ecology of these organisms can help us understand the nature of human relationships,The basic laws that govern the exchange relationships between living organisms in general should also form the basis of human behavior. The study of ecology is extremely complex, but by examining plant life in the desert - a relatively less complex case - some generalizations about behavior can be drawn.
Keywords: Animal behavior; Plant behavior; Ecology; Exchange relationships between living organisms; Examination of desert plant life